Expressed emotion and long‐term outcome among adolescents with anorexia nervosa. Issue 11 (22nd September 2021) - Rienecke, Renee D.; Gorrell, Sasha; Blalock, Dan V.; Smith, Kathryn; Lock, James; Le Grange, Daniel
Abstract: Objective: The purpose of the current study is to examine expressed emotion (EE) and long‐term treatment outcome among adolescents participating in a randomized controlled trial (RCT) for treatment of anorexia nervosa (AN). It was hypothesized that patients with high EE parents at baseline would show more severe symptoms at end‐of‐treatment, 12‐month follow‐up, and 4‐year follow‐up than patients from low EE families. Method: Secondary data analysis was conducted of original RCT data from a two‐site eating disorder treatment trial conducted in the United States. Participants were 121 adolescents with AN who completed measures of EE, eating disorder psychopathology, depression, and self‐esteem. Results: Generalized estimating equations showed that participants who were in the Low EE group achieved a more accelerated drop in depression scores in the context of treatment (first 12 months) than participants in the High EE group. No other significant Group × Time interactions were found. Discussion: Findings suggest that high parental EE at baseline does not indicate that adolescent patients with AN will fare poorly 4 years later.